Identification of the ADH gene family in Trichosporon asahii and the role of TaADH_like in pathogenicity and fluconazole resistance - Zhen Liu; Xiaoping Ma; Xiangwen Zeng; Zhiguo Li; Ruiguo Liu; Rongyan Luo; Weichen Wang; Muhammad Salman Tahir; Chengdong Wang; Yu Gu (BMC Genomics)
Abstract Alcohol dehydrogenase has been studied in regulation of fungal growth and development, stress response and pathogenesis, but its function in T. asahii remains unexplored. In this study, we analyzed the ADH gene family in T. asahii for the first time, identifying six ADH genes and containing conserved ADH_N and ADH_Zinc_N domains. We constructed an overexpression strain of the most significantly differentially expressed gene TaADH_like and compared its phenotypes with those of the wild-type strain, focusing on colony morphology, biofilm biomass, stress response, drug resistance, and pathogenicity. The results showed that TaADH_like overexpression reduced sensitivity to hypoxic conditions, altered the hyphae-to-yeast transition, and led to slower growth, decreased colonization ability, reduced tissue damage, and lower lethality. Increased osmotic stress sensitivity and the involvement of the HOG MAPK pathway in the hyphae-to-yeast conversion contributed to the reduced colonization capacity of T. asahii. Furthermore, the overexpression of TaADH_like promoted biofilm formation and led to a slight enhancement in fluconazole resistance in T. asahii. This study is the first to elucidate the function of the alcohol dehydrogenase gene in T. asahii, providing a foundation for future genetic research on this pathogen.